2020
DOI: 10.1080/09669582.2020.1742725
|View full text |Cite
|
Sign up to set email alerts
|

Nature tourism and mental health: parks, happiness, and causation

Abstract: Park tourism is correlated with better mental health, with high economic value, but some aspects of causal mechanisms have remained unresolved. I interviewed 238 outdoor nature and adventure tourists of all ages and backgrounds, at subtropical national parks in Queensland, Australia. I asked whether they visit parks because they are happy, or they are happy because they visit parks. A large majority, 82%, picked the latter. Of those asked, 87.5% reported short-term emotional benefits; 60%, medium-term recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(73 citation statements)
references
References 69 publications
4
49
0
1
Order By: Relevance
“…Research (e.g. Buckley, 2020, Corkery, 2004Tarrant, 1996;Ulrich, 1979;Weinstein et al, 2009) shows that being in nature increases physical, mental and spiritual health and wellbeing. Some researchers suggest how to motivate people to engage with nature (Kaplan & Kaplan, 1989;Mitchell & Popham, 2007;Takano et al, 2002), but not much research has dug into the issue of what nature 'is' to older people.…”
Section: Discussionmentioning
confidence: 99%
“…Research (e.g. Buckley, 2020, Corkery, 2004Tarrant, 1996;Ulrich, 1979;Weinstein et al, 2009) shows that being in nature increases physical, mental and spiritual health and wellbeing. Some researchers suggest how to motivate people to engage with nature (Kaplan & Kaplan, 1989;Mitchell & Popham, 2007;Takano et al, 2002), but not much research has dug into the issue of what nature 'is' to older people.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived well-being is defined as an "assessment of satisfaction with the quality of their life (QOL) as a whole and/or the quality of aspects or domains of life" (McCabe & Johnson, 2013, p. 44). In a context of leisure travel, tourists resort to vacations for health and wellness benefits (Buckley, 2020;Farki c et al, 2020;Hanna et al, 2019), in which wellness has been referred to as an "optimistic assessment of their lives including contentment, positive emotion, engagement and purpose" (Pyke et al, 2016, p. 94). Tourists' traversal of a foreign place and encounter of hospitality services often renders mental and fatigue restoration potential that ultimately enhances their temporal well-being (Rosenbaum & Wong, 2015).…”
Section: Proposed Research Frameworkmentioning
confidence: 99%
“…Tourists' traversal of a foreign place and encounter of hospitality services often renders mental and fatigue restoration potential that ultimately enhances their temporal well-being (Rosenbaum & Wong, 2015). In this sense, travel-induced well-being includes an elicited life satisfaction with physical and mental fitness, thanks to temporary respite from daily stress that helps individuals to recuperate and rejuvenate (Buckley, 2020;Hanna et al, 2019;Strauss-Blasche et al, 2005).…”
Section: Proposed Research Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact with nature is related to human well-being and health (Bratman et al, 2012;Martin et al, 2020). Several scientific studies have demonstrated the positive effects of exposure to green, such as reducing stress, feeling of happiness, improving recovery from surgery, reducing vascular diseases, practicing physical activities, mental health, among other benefits (Chang and Chen, 2005;Keniger et al, 2013, Buckley, 2020Fagerholm et al, 2020).…”
Section: Contact With Naturementioning
confidence: 99%